Research and documentation in the development sciences in the English-speaking Caribbean - Greene, J.E. (Institute of Social and Economic Studies KingstonJM, 1977)
Aims to devise a strategy for acquiring, organising, controlling bibliographically and disseminating development sciences information in response to the needs of various users.